HUMAN CAPITAL IN ORGANIZATIONS - Marisol Castillo Álvarez; Janisleydis Rodríguez Alarcón (Universitas Nusa Cendana, 2016)
The present material addresses an essential issue for Cuban companies : the need for the functioningof the companies Human Capital development that they count on. That is why the implementationof the System of Management and Management in state enterprises and senior managementorganizations must achieve a significant organizational change within the same and fully managedthe systems that comprise it. In this sense, the Human Capital Management System plays a veryimportant role since the success of any venture depends mainly on the flexibility and capacity forinnovation that the PEOPLE involved in the organization have. Reflect on the Human CapitalManagement as well as the integration of several processes taking into account that the HC is themain asset of the company and therefore the most competitive resource is the purpose of this work.Keywords: Organization, Human Capital, Human Capital Management System, LaborCompetencies.